Muatan linkungan hidup pada sekolah adiwiyta smpn 13, Pasir Putih, Manokwari, Papua Barat - Bawole, Roni; Insen, Selmina; Krey, Keliopas; Mudjirahayu (Cassowary, 2025)
ABSTRACT : The Adiwiyata School Program is environmental education in an effort to overcome environmental problems, which is applied to learning participants in order to gain knowledge, skills, caring attitudes, commitment, safeguarding, caring for, improving and utilizing the environment wisely. Therefore, this research aims to analyze the environmental content and achievement of environmental content at Adiwiyata schools. Research using descriptive techniques was carried out at the Adiwiyata School, 13 Pasir Putih junior high school, Manokwari for 3 months of field activities in September – November 2023. The results of the research have shown that the environmental content of the Adiwiyata school is very dependent on the development of environmentally sound policies, the development of an environmentally based curriculum. , participatory-based environmental development, developing environmentally friendly supporting infrastructure. Achieving the environmental content of Adiwiyata schools depends on the attitude of students who really care about the environment. The aspect of maintaining cleanliness with the highest indicator of waste management, while the lowest is the aspect of maintaining cleanliness, water conservation, used goods innovation results, and counseling guidance. Collaboration between stakeholders at the Adiwiyata school is the responsibility of all parties together in efforts to preserve and save the environment and sustainable development.